Evaluating the catalytic effect of Fe@Fe2O3-modified granulated cork as an innovative heterogeneous catalyst in electro-fenton degradation of benzoquinone in different aqueous matrices - do Vale-Júnior, Edilson; de Sousa, Rainy Alves; Antunes, Renato Altobelli; do Nascimento, Jose Heriberto Oliveira; Lima Santos, José Eudes [UNESP]; Martínez-Huitle, Carlos A. [UNESP]; dos Santos, Elisama Vieira [UNESP] (Elsevier, 2023)
This study investigated the potential of a novel biomass-derived cork as a suitable catalyst after its modification with Fe@Fe2O3 for in-situ application in heterogeneous electro-Fenton (HEF) process for benzoquinone (BQ) elimination from water. No attempts on the application of modified granulated cork (GC) as a suspended heterogeneous catalyst in the HEF process for water treatment have been published yet. GC was modified by sonification approach in a FeCl3 + NaBH4 solution to reduce the ferric ions to metallic iron in order to obtain Fe@Fe2O3-modified GC (Fe@Fe2O3/GC). Results clearly demonstrated that this catalyst exhibited excellent electrocatalytic properties, such as a high conductivity as well as relatively high redox current and possessed several active sites for water depollution applications. Using Fe@Fe2O3/GC as catalyst in HEF, 100% of BQ removal was achieved in synthetic solutions by applying 33.3 mA cm−2 after 120 min. Different experimental conditions were tested to determine that best possible conditions can be as follow: 50 mmol L−1 Na2SO4 and 10 mg L−1 of Fe@Fe2O3/GC catalyst using Pt/carbon-PTFE air diffusion cell by applying 33.3 mA cm−2. Nevertheless, when Fe@Fe2O3/GC was used in the HEF approach to depollute real water matrices, no complete BQ concentration was removal achieved after 300 min of treatment, achieving between 80 and 95% of effectiveness.
Keywords: Benzoquinone; Cork; Heterogeneous electro-Fenton; Sustainable process